New Control Approach of Multicell Stacked Cell Inverter for Solar Photovoltaic System - François Yonga; Colince Welba; Abdouramani Dadjé; Noël Djongyang (International Journal of Photoenergy, 2022)
This paper presents the study, modelling, and simulation of the DCSVM (Duty Cycle Space Vector Modulation) control technique applied to a new inverter topology dedicated to isolated or grid-connected photovoltaic systems using the MATLAB/Simulink software. This inverter is based on the structures of a stacked multicell converter (SMC) and an H-bridge. This new topology allows the voltage stresses of the converter to be distributed among several switching cells. It also allows the input voltage to be divided into several fractions so that the number of switching power semiconductors is reduced. The DCSVM is a control technique that generates control signals to the two-level voltage converter as well as the intermediate times. The main advantage of this control technique is the reduction in the number of calculations, especially for the trigonometric functions and the generation of the reference voltage. In this contribution, the general topology of this microinverter is described and the DCSVM control technique is presented. Finally, simulation results, the efficiency of this topology, and the validity of the DCSVM control in a grid-connected PV generation system are discussed. The results obtained are very satisfactory.